Innovative Blended Learning Curriculum in Noninvasive Ventilation for Pulmonary and Critical Care Fellows - Daoud, Asil; Cramer-Bour, Cassondra; Venkat, Divya; Sankari, Abdulghani (Avicenna Journal of Medicine, 2025)
There is a lack of a standardized curriculum for the appropriate use of noninvasive ventilation (NIV), which is readily accessible. Management of NIV is a core competency for physicians training in pulmonary and critical care medicine (PCCM). We present a blended model of instruction that was highly successful in our pilot program.The curriculum targeted eight first-year PCCM fellows to assess knowledge and confidence in key competencies of NIV management. After a baseline assessment, fellows engaged in both hands-on instruction and traditional didactics in NIV. Following, fellows were encouraged to use the e-learning modules for enhanced instruction. The modules were designed to cover all major aspects of NIV management and with unique interactive patient cases for both inpatient and outpatient uses of NIV.Eight first-year PCCM fellows completed the training and responded to the posttest assessment 4 weeks later. The average multiple-choice questions (MCQs) score increased from 13.5 ± 3.2 (54.0%) to 18.4 ± 1.6 (73.6%) and was significant (p = 0.004). A Likert assessment of learner confidence also showed significant improvement across several key competency domains.This curriculum represents a successful and novel approach to NIV education, a critical but challenging core competency in pulmonary medicine for physicians training in PCCM.
Keywords: noninvasive ventilation; hypoxic respiratory failure; hypercapnic respiratory failure; blended learning; graduate medical education